Improving Fourth Industrial Revolution (IR 4.0) Implementation among Skilled Workers in the Construction Industry - Go, Alvin Zhi Ying; Kasim, Narimah; Zainal, Rozlin; Abd Rahim, Mohd Hilmi Izwan; Omar, Abdul Halim (Research in Management of Technology and Business, 2023)
As the COVID-19 pandemic, the construction industry’s operating process have changed, which accelerates the construction industry to move toward Industrial Revolution 4.0. Furthermore, skills that have been thought would endure over time could quickly become obsolete among skilled workers, and upskilling the skilled workers will face formidable challenges arising from the influx of new technologies. Therefore, this research was undertaken to identify challenges, influencing factor, and steps to improve the IR 4.0 implementation among skilled workers in the construction industry. To accomplish the objectives, the study was carried out with the quantitative approach by using questionnaire as the instrument to collect the primary data. There were 248 respondents among G7 contractors selected at Johor state for this research and 145 respondents have been successfully collected. Statistical Package for the Social Science (SPSS) software was utilised to analyse the collected data in descriptive methods to determine the frequency and mean score values. Besides, secondary data information was obtained through various references such as journal, article, website or report related to IR 4.0 implementation among skilled workers in construction industry. Moreover, the result showed that the biggest challenge of the IR 4.0 implementation was insufficient of skilled workers, and the influencing factor of IR 4.0 implementation was to reduce the project activity errors, as well as the step to improve IR 4.0 implementation was providing the training program. In conclusion, this research provided a better understanding of the potential of IR 4.0 implementation for improving construction’s skilled workers.